Influence of Selected Macroeconomic Variables on Economic Growth in Nigeria (1999 – 2018) - Etale, Lyndon M.; Imbazi, Lucky L. (Advances in Social Sciences Research Journal, 2020)
This study set out to empirically examine the influence of selected microeconomic variables (MEVs) on economic growth in Nigeria between 1999 and 2018. It evaluated gross domestic product (as the measure of economic growth) as a function of four selected variables of MEVs: Interest rate, Exchange rate, Inflation and Broad Money Supply. For effective and efficient analysis of the study variables the multiple regression technique based on the ordinary least square method with the help of several inferential statistical tools were used for data analysis to draw necessary conclusions. The models used analyze the relationship between the selected MEVs. Nigeria’s inability to increase her GDP over the years far above her population growth is heavily dependent on the sincerity of our political will to actualize it. The hypotheses formulated were rejected for three variables because the critical P-value 0.05 is < the calculated P-values; except for BMS Broad Money Supply (BMS) which revealed significant positive influence on GDP with P-value of 0.00 < 0.05 level of significance. The study therefore concluded that macroeconomic decision is not enough to bring about economic growth. The interplay of both fiscal and monetary policy backed up with political will to achieve its objectives both in the short and long-run is required. Nigeria still lack good political will for economic growth and poor governance. Still government should improve the regulations and supervisory role in the financial sector for sustainable growth to be achieved in Nigeria.